Multimedia dan islam penyunting Abu Bakar Abdul Majeed, Siti Fatimah Abdul Rahman. - ABU Bakar Abdul Majeed; SITI Fatimah Abdul Rahman; Siti Fatimah Abdul Rahman.; Abu Bakar Abdul Majeed. (Institut Kefahaman Islam Malaysias, 2000)
On Malaysian Muslim community and issues on multimedia computing; collection of articles.